Solidarity with the Oppressed, Conversions, Truth in Action: Gregory Baum’s Evolving Theological Horizons - Cormie, Lee (Théologiques, 2021)
Gregory Baum was not a great theologian like the systematic giants of the mid-20th century. Rather, in a rapidly changing world which no one single person, group or discourse can fully grasp, he was a different kind of theologian, in dialogue with expanding circles of others, exploring new interdisciplinary pathways, forging another kind of theology witnessing to hope that another world is possible.